A case report of ruptured ovarian ectopic pregnancy - Elizabeth, Kitty; Venugopal, Arya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ectopic implantation of the fertilized egg in the ovary is rare. Most prominent risk factors of ovarian pregnancy are IVF and IUD. Its incidence after natural conception ranges from 1 in 2000 to 1 in 60 000 deliveries and accounts for 3% of all ectopic pregnancies. We presented a case of right ruptured ovarian ectopic pregnancy managed laparoscopically. Histopathological examination confirmed the diagnosis.